Slavery, the British Atlantic economy and the industrial revolution - Harley, CK (University of Oxford, 2013)
Modern economic growth first emerged in Britain about the time of the Industrial Revolution, with its cotton textile factories, urban industrialization and export orientated industrialization. A period of economic growth, industrial diversification and export orientation preceded the Industrial Revolution. This export orientation revolved around an Americanization of British trade for which the slave colonies of the Caribbean were central. The Eric Williams’ explored the extent to which this export economy based on West Indian slavery contributed to the coming of the Industrial Revolution. His claim that profits from the slave trade were crucial to the Industrial Revolution has not stood up to critical evaluation. Nonetheless, modern speculations regarding endogenous growth plausibly postulate that manufacturing, urbanization, and a powerful merchant class all have a favourable impact for growth. These hypotheses need careful consideration.